sistem kontroling biaya dan pemakaian air PDAM berbasis internet of thinks menggunakan wemos d1 dan blynk: Kontroling Biaya dan Pemakaian Air PDAM - ambika, rully; Sudianto (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
ABSTRACTThe need for clean water is increasing, especially in urban areas, where it is becoming a scarce commodity and has commercial value. The government-owned Drinking Water Company (PDAM), commonly known as the "Drinking Water Company," provides and meets the clean water needs of residents, government agencies, and businesses in urban areas. However, obtaining this clean water supply inevitably incurs costs. For agencies or businesses, this clean water consumption is a significant expense that requires careful consideration. Therefore, water consumption requires judicious use to avoid inflated water bills. Therefore, an automated tool is needed to help control PDAM water usage and maintain stable costs. By utilizing an internet-based system, the tool will make it easier for users to manage and control PDAM water usage remotely. The tool uses a Wemos D1 microcontroller and the BLYNK application as a supporting system that can be operated via a smartphone with the help of an internet connection.